2015
DOI: 10.1007/430_2015_178
|View full text |Cite
|
Sign up to set email alerts
|

The Electronics of CH Activation by Energy Decomposition Analysis: From Transition Metals to Main-Group Metals

Abstract: Alkane CH activation is a fundamental reaction class where a metalligand complex reacts with a CH bond to give a metal-alkyl organometallic intermediate. CH activation reactions have been reported for a variety of transition metals and main-group metals. This chapter highlights recent quantum-mechanical studies that have used energy decomposition analysis (EDA) to provide insight into σ-coordination complexes and transition states for alkane CH activation reactions. These studies have provided new conceptual u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
(59 reference statements)
2
3
0
Order By: Relevance
“…Using energy decomposition analysis, we previously highlighted the electrophilic nature of Tl III in alkane C−H activation transition states that results from the dominant interaction between the Tl III 6s LUMO and a filled C−H σ bond. 20 Our description of Tl III acetate complexes is also consistent with the report by Bickelhaupt, who showed that there is minimal d-orbital participation in bonding in maingroup complexes. 21 In this work three major Tl III complexes were examined: Tl III (OAc) 3 , (OAc) 2 Tl III (CH 3 ), and (OAc)Tl III (CH 3 ) 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Using energy decomposition analysis, we previously highlighted the electrophilic nature of Tl III in alkane C−H activation transition states that results from the dominant interaction between the Tl III 6s LUMO and a filled C−H σ bond. 20 Our description of Tl III acetate complexes is also consistent with the report by Bickelhaupt, who showed that there is minimal d-orbital participation in bonding in maingroup complexes. 21 In this work three major Tl III complexes were examined: Tl III (OAc) 3 , (OAc) 2 Tl III (CH 3 ), and (OAc)Tl III (CH 3 ) 2 .…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…In contrast, high-oxidation-state Tl III complexes have a core d 10 electronic configuration with a low-energy empty 6s orbital that determines oxidation states and reactivity. Using energy decomposition analysis, we previously highlighted the electrophilic nature of Tl III in alkane C–H activation transition states that results from the dominant interaction between the Tl III 6s LUMO and a filled C–H σ bond . Our description of Tl III acetate complexes is also consistent with the report by Bickelhaupt, who showed that there is minimal d-orbital participation in bonding in main-group complexes …”
Section: Resultssupporting
confidence: 88%
“…However, the general features of these orbital interactions suggest that this C−H activation transition state should be described as an electrophilic substitution similar to other transition-metal acetate transition states. It is also noteworthy that energy decomposition analysis suggests that the interaction between Tl III (TFA) 3 and ethane has nearly equal covalent (orbital) and electrostatic character, 88 which can be described by the partial charges shown in Scheme 8b.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, these two complexes are predicted to have large barriers for methane dissociation (∼13 kcal mol −1 by the M05-2X results). Fluorinated phosphines are poorer donors to metal centers than analogous alkyl-substituted phosphines. , The computational result for complexes of the (CF 3 ) 2 PCH 2 P(CF 3 ) 2 and (CF 3 ) 2 PCF 2 P(CF 3 ) 2 phosphines is therefore consistent with our expectation that the methane complex 2 should be stabilized relative to the methyl/hydride complex 1 if the ancillary ligands are less electron-donating than those we previously studied experimentally; other theoretical studies also support this idea. …”
Section: Discussionmentioning
confidence: 97%